Dose‐exposure‐response of CARDALIS® (benazepril/spironolactone) on the classical and alternative arms of the renin‐angiotensin‐aldosterone system in healthy dogs - Elizabeth Manson; Jessica L. Ward; Maria Merodio; Emilie Guillot; Thomas Blondel; Karin Allenspach; Oliver Domenig; Jonathan P. Mochel (Journal of Veterinary Internal Medicine)
Abstract Background Benazepril exhibits a dose‐dependent effect on biomarkers of the circulating renin‐angiotensin‐aldosterone system (RAAS) in dogs. Hypothesis/Objectives To characterize the dose‐exposure‐response relationship of a fixed‐dose combination product including benazepril and spironolactone (CARDALIS®) on RAAS biomarkers in dogs. Animals Eighteen purpose‐bred healthy beagle dogs. Methods Three groups of 6 dogs received different doses of CARDALIS® for 14 days following induction of RAAS activation by feeding a low‐sodium diet: (a) benazepril 0.25 mg/kg + spironolactone 2 mg/kg PO q24h (label dose); (b) benazepril 0.25 mg/kg + spironolactone 2 mg/kg PO q12h; or (c) benazepril 0.5 mg/kg + spironolactone 4 mg/kg PO q12h. Blood samples were collected at baseline and serial time intervals after CARDALIS® dosing to measure serum RAAS biomarkers and plasma concentrations of active drug metabolites. Time‐weighted averages for serum RAAS biomarkers after CARDALIS® dosing at steady state were compared between dosage groups using Wilcoxon rank‐sum testing. Results Compared to the label dose, the highest dose of CARDALIS® was associated with a 30% decrease in angiotensin II (P = .03), 94% increase in angiotensin 1‐7 (P = .03), 71% decrease in surrogate activity of ACE (P = .002), and 116% increase in circulating aldosterone (P = .02). CARDALIS® was well‐tolerated at all doses with no clinically relevant changes in renal values or serum electrolytes. Conclusions and Clinical Importance The combined CARDALIS® product leads to dose‐dependent alterations of RAAS metabolites. These results could help inform clinical trials in dogs with heart disease.